Economic Analysis Positioning of Risks at the Stages of Company Development - Khairullina, Albina Dzhavdatovna; Skutelnik, Anastasiya Alexandrovna (International Journal of Criminology and Sociology, 2022)
The purpose of the article is economic analysis and compare the organization's risks to the stages of the life cycle according to I. K. Adizes. This paper uses risk classifications of V. S. Romanov and Microsoft. Based on the description of each stage of the organization's development, an attempt is made to systematize risks at each stage of the company's life cycle according to the model of Yitzhak Adizes. In addition, risk maps have been drawn up for the company's development stages. The authors of the article argue the need for this research by the fact that at the moment risk management in companies occurs without taking into account the life cycle, respectively, those groups of risks that are characteristic of the stage of development of the company are overlooked. This is why life-cycle risk management is necessary: companies will have a list of risks that are specific to the stage of development of the organization.